Relationship between Self-Regulated Learning and Reading Skills Ability for Arabic Language and Literature Study Program Students in East Java/Al-‘Alāqah bayna Al-Ta - Lailatul Qomariyah; Usfiyatur Rusuly; Ade Destri Deviana (Universitas Islam Negeri Palangka Raya, 2021)
Reading skills require Self-Regulated Learning (SRL) in student which is very important to achieve success in this competency. With SRL, students will know what strategies they must do to achieve these competencies. The purpose of this article is to reveal: 1) Correlation between Self-Regulated Learning with student reading skills. This article used quantitative method. The study sample consisted of 168 students of the Arabic Language Study Program and Literature in Malang. The research data was obtained from questionnaire, and test. The quantitative data analysis method uses Pearson correlation analysis. The results showed that there was a correlation between Self-Regulated Learning and reading skills with a correlation coefficient category of 0.357 which was categorized as strong enough. The results of the Self-Regulated Learning variable indicate that implementing aspect is the dominant aspect that can be seen. Of the highest loading factor value. The results of this study provide input for Arabic language teachers to train their students to think critically in reading activities so that they are motivated to have independence in producing messages from reading.